Rivaroxaban for extended thromboprophylaxis in acutely ill medical patients 75 years of age or older. (17th August 2021) - Ageno, Walter; Lopes, Renato D.; Goldin, Mark; Yusen, Roger D.; Albers, Gregory W.; Elliott, Gregory C.; Halperin, Jonathan L.; Hiatt, William R.; Maynard, Gregory; Steg, Philippe Gabriel; Weitz, Jeffrey I.; Suh, Eunyoung; et al.
Abstract: Background: Although older patients are at increased risk for venous thromboembolism (VTE), thromboprophylaxis is underused because of bleeding concerns. The MARINER trial evaluated whether rivaroxaban reduced symptomatic postdischarge VTE in acutely ill medical patients. Objectives: We hypothesized that rivaroxaban would have a favorable benefit/risk profile in patients ≥75 years of age. Methods: Patients were randomized in a double‐blind manner at hospital discharge to rivaroxaban (10 mg/day for creatinine clearance ≥50 ml/min; 7.5 mg/day for ≥30‐<50 ml/min) or placebo for 45 days. Using a Cox proportional hazard model including treatment as a covariate, we compared the risk of the primary efficacy outcome (symptomatic VTE plus VTE‐related death in the intention‐to‐treat population) and safety outcome (International Society on Thrombosis and Haemostasis major bleeding in the safety population) in the prespecified subgroups of patients ≥ and <75 years of age. Results: The primary event rate in patients ≥75 years of age was 2‐fold higher than that in those <75 years. The incidence of the primary efficacy outcomes in both age groups was numerically lower with rivaroxaban than with placebo (≥75: 1.2% and 1.6%, HR 0.73, 95% CI 0.43‐1.22; <75 0.6% and 0.8%, HR 0.78, 95% CI 0.46‐1.32; interaction p ‐value for age group = .85). The incidence of major bleeding was low and similar in the two age and treatment groups (interaction p value for age group = .35). Conclusion: Symptomatic VTE and VTE‐related death occur frequently in older patients with acute medical illness. The benefit/risk profile of rivaroxaban in patients ≥75 years of age appears consistent with that observed in the general population.